Compound usage of twisted tape turbulator and air injection for heat transfer augmentation in a vertical straight tube with upward stream. (June 2021) - Moria, Hazim
Abstract: In this paper, the effect of combined usage of twisted tape turbulators and air injection on the heat transfer augmentation was probed. The tube was under heat flux, which was produced using heater wire. Three twisted tapes with three different pitches were used for conducting the experiments. In order to better understand the flow properties, the flow patterns were recorded utilizing a Canon SX540 camera. Flow patterns, pressure drop, heat transfer coefficient, and cost per benefit ratio factors were the parameters that were studied in this paper. Results showed that the patterns of two-phase flow in the presence of twisted tape turbulator are significantly different from those of smooth tubes. Besides, a significant increment in the heat transfer and pressure drop was observed. It was found that air injection could lead up to 30.3% and 62% increment in the heat transfer coefficient and pressure drop, respectively. The best values of the cost per benefit ratio (C.B.R) factor was about 0.93 and was occurred at the air and water flow rate of 1 and 5 lit/min. This value was reached at the twisted tape turbulator with the largest pitch.